2011
DOI: 10.1186/1477-7517-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Selling sex in unsafe spaces: sex work risk environments in Phnom Penh, Cambodia

Abstract: BackgroundThe risk environment framework provides a valuable but under-utilised heuristic for understanding environmental vulnerability to HIV and other sexually transmitted infections among female sex workers. Brothels have been shown to be safer than street-based sex work, with higher rates of consistent condom use and lower HIV prevalence. While entertainment venues are also assumed to be safer than street-based sex work, few studies have examined environmental influences on vulnerability to HIV in this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 31 publications
2
94
0
Order By: Relevance
“…16,19,28,29 Ang and Morisky 19 found that FSW who worked in an entertainment venue with a mandatory condom use rule (46.6% had rule) had a higher level of condom use. Condom availability in a venue was also associated with use, 16,28 and Haseen et al 15 found that young male clients of FSW were more likely to use condoms if use was negotiated by the FSW.…”
Section: Condom Usementioning
confidence: 97%
See 2 more Smart Citations
“…16,19,28,29 Ang and Morisky 19 found that FSW who worked in an entertainment venue with a mandatory condom use rule (46.6% had rule) had a higher level of condom use. Condom availability in a venue was also associated with use, 16,28 and Haseen et al 15 found that young male clients of FSW were more likely to use condoms if use was negotiated by the FSW.…”
Section: Condom Usementioning
confidence: 97%
“…Perceptions of risk may reflect general cultural norms rather than subcultural sexual partnering, for example, a man who does not consider himself gay may not perceive himself at a higher risk, if engaging in MSM sex or entertainment-based SW may not consider themselves as SW and therefore not conform to occupational norms of SW such as condom use. 29 Also from the literature reviewed, transgendered persons are more likely to practice anal sex. Prevention information has to be tailored to individual perceptions and constructions of self and the interplay between subcultural roles and behaviors and normative societal behavior.…”
Section: Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a systematic review of the effectiveness of 28 HIV interventions among sex workers found that access to STI services and condom promotion decreases the burden of STIs among sex workers and that policy support for such interventions improves intervention efficacy (Shahmanesh et al 2008) Violence, perpetrated both by clients and authorities, is an unfortunate mainstay of criminalised sex work. Street-based sex work, which is especially common where sex work is criminalised, has been associated with higher levels of client violence than working indoors (Maher et al 2011). Due to threats of arrest in criminalised settings, sex workers frequently migrate from known, well-populated areas to isolated locales where client violence is more likely to occur and negotiation of condom use less likely (KrĂŒsi et al 2012).…”
Section: Criminalisationmentioning
confidence: 99%
“…In recent years, significant economic and policy changes have affected the sex work landscape, with notable shifts in sex work venues, typologies and more women being engaged in transactional sex than ever before. [16][17][18][19][20] Until 2008, FSW in Cambodia were categorised as 'direct' and were mostly brothel-based, or 'indirect'. Indirect FSW were distinguished from direct FSW, generally working in entertainment establishments as beer promotion girls, waitresses, hostesses or karaoke girls, for example, and engaged in occasional transactional sex for supplementary income.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%